De Luxuria Propagata Romana Aetate. Roman Luxury in Its Many Forms - Pons Pujol, Lluís (Archaeopress, 2023)
This book focuses on luxonomics, or the economy of luxury in Roman times, and how its study is an element that is essential to understanding the history of the period. Organised in chronological order, the evolution of the luxury economy is divided into areas of consumption, production, and criticism.